2005
DOI: 10.1038/nrn1765
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system injury-induced immune deficiency syndrome

Abstract: Infections are a leading cause of morbidity and mortality in patients with acute CNS injury. It has recently become clear that CNS injury significantly increases susceptibility to infection by brain-specific mechanisms: CNS injury induces a disturbance of the normally well balanced interplay between the immune system and the CNS. As a result, CNS injury leads to secondary immunodeficiency - CNS injury-induced immunodepression (CIDS) - and infection. CIDS might serve as a model for the study of the mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
702
5
21

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 813 publications
(754 citation statements)
references
References 133 publications
26
702
5
21
Order By: Relevance
“…Another attractive feature of using Kv1.3 inhibitors to reduce neuroinflammation in the wake of ischemic stroke is that Kv1.3 inhibitors are known to be immunomodulators rather than immunosuppressants and do not impair the ability of rodents to clear acute infections or of primates to develop vaccine responses 5, 8. Kv1.3 inhibitors are therefore unlikely to further increase the risk of respiratory and urinary tract infections, which are responsible for considerable morbidity and mortality after stroke 45, 49. This phenomenon, which manifests as lymphopenia in stroke patients and rodent models, is mediated by an increased release of cortisol and catecholamines,49 which has recently been shown to induce a higher bone marrow output of inflammatory monocytes and neutrophils and a drastic reduction in lymphoid progenitors 50.…”
Section: Discussionmentioning
confidence: 99%
“…Another attractive feature of using Kv1.3 inhibitors to reduce neuroinflammation in the wake of ischemic stroke is that Kv1.3 inhibitors are known to be immunomodulators rather than immunosuppressants and do not impair the ability of rodents to clear acute infections or of primates to develop vaccine responses 5, 8. Kv1.3 inhibitors are therefore unlikely to further increase the risk of respiratory and urinary tract infections, which are responsible for considerable morbidity and mortality after stroke 45, 49. This phenomenon, which manifests as lymphopenia in stroke patients and rodent models, is mediated by an increased release of cortisol and catecholamines,49 which has recently been shown to induce a higher bone marrow output of inflammatory monocytes and neutrophils and a drastic reduction in lymphoid progenitors 50.…”
Section: Discussionmentioning
confidence: 99%
“…This early immune activation often progresses to immune suppression in patients with stroke. Some studies have suggested that lymphopenia and immunosuppression occur as a compensatory mechanism against brain damage by attenuating autoreactive T-cell targeting of CNS self-antigens [14,15]. Other studies have demonstrated that stroke-induced immune suppression increases the risk of secondary infections and increases mortality rates in patients [16,17].…”
Section: Impact Of Stroke On Immunitymentioning
confidence: 99%
“…The signals and mechanisms that trigger the SNS and the HPA to induce stroke-induced immunodepression remain unclear. One cause appears to be the increased pro-inflammatory cytokine production that occurs early after stroke and central nervous system (CNS) injury-specific neurogenic signaling (for review see Dirnagl et al, 2007;Meisel et al, 2005). An early study by Prass et al (2003) blocked the SNS and HPA by administration of a b-adrenoceptor antagonist (propranolol) and a glucocorticoid receptor inhibitor (RU486), respectively.…”
Section: Stroke-induced Immunodeficiency Syndromementioning
confidence: 99%